Fracture of hierarchical multi-layered bioinspired composites. (February 2022) - Magrini, Tommaso; Senol, Ayca; Style, Robert; Bouville, Florian; Studart, André R.
Abstract: Lightweight composites have revolutionized the sector of aircrafts and will continue to play a major role in future energy-efficient transportation systems. However, the design of composites featuring high strength and high fracture toughness remains challenging due to the usual trade-off between these properties in synthetic materials. Inspired by the strong and tough hierarchical architecture of mollusk shells, we create tough composites by combining soft polymer layers with alternating, nacre-like layers that are infiltrated with the same polymer. Here, we study the fracture behavior and the toughening mechanisms underlying the high crack growth resistance of these hierarchical composites. Polymer layers with different stiffness and yield strength were designed in order to evaluate the effect of plastic deformation and bridging of the polymer phase on the early and late stages of the fracture process. Controlled fracture experiments allowed us to visualize the interactions of a propagating crack with the hierarchical architecture and to quantify the resistance of the polymer layer against early-stage fracture. Our findings provide new insights into the interplay of multiscale toughening mechanisms in hierarchical bioinspired architectures and offer guidelines for the design and manufacturing of strong and tough lightweight composites.